2018
DOI: 10.3384/lic.diva-144491
|View full text |Cite
|
Sign up to set email alerts
|

Additively Manufactured Inconel 718 : Microstructures and Mechanical Properties

Abstract: Linköping 2018Cover image: A fracture surface of EBM IN718 after tensile test at room temperature.During the course of research underlying this thesis, Dunyong Deng was enrolled in Agora Materiae, a multidiciplinary doctoral program at Linköping University, Sweden. Printed by LiU-Tryck 2018 © Dunyong Deng AbstractAdditive manufacturing (AM), also known as 3D printing, has gained significant interest in aerospace, energy, automotive and medical industries due to its capabilities of manufacturing components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 162 publications
(227 reference statements)
4
46
0
Order By: Relevance
“…The δ phase is a brittle phase which consumes the strength, inducing Nb in the alloy. This transformation might hinder the high-temperature applications of IN718, where characteristics like tensile and yield strengths are important [8]. From the Pareto chart in Figure 9, it is clear that the scan speed is the dominant factor in determining the percentage of γ" in the as-built samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The δ phase is a brittle phase which consumes the strength, inducing Nb in the alloy. This transformation might hinder the high-temperature applications of IN718, where characteristics like tensile and yield strengths are important [8]. From the Pareto chart in Figure 9, it is clear that the scan speed is the dominant factor in determining the percentage of γ" in the as-built samples.…”
Section: Discussionmentioning
confidence: 99%
“…IN718 is composed of chromium, molybdenum, aluminum, titanium, cobalt, niobium, and nickel, with nickel being the highest proportion. The commonly seen phases in IN718 are γ, γ', γ", δ, MC, and laves [8]. The major phase of IN718 is the gamma (γ) phase, as it is mainly comprised of Ni and forms an austenitic face-centered-cubic (FCC) matrix [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways to deal with the formation of the Laves phase and hot cracking. Deng et al [15] determined that a slight variation in the Nb, Ni and Ti composition of IN718 feed wire, decreases the formation of the Laves phase and improves the mechanical properties of the WAAM IN718. Xu et al [16] reported that the postdeposition homogenization heat treatment not only dissolves the Laves phase back into the matrix but improves the microstructure and elastic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Alloy 718 stands out for its high strength, corrosion resistance, a wide operating temperature spectrum (from cryogenic up to around 650°C), and notably good welding characteristics. [5,6] However, such high-performance materials often suffer from difficulties during fabrication. Castings, for example, typically exhibit coarse, segregated, and porous microstructures which require homogenization and densification to reach the requirements for critical components.…”
Section: Introductionmentioning
confidence: 99%